Legions of Presentations of Myxedema Coma: A Case Series from a Tertiary Hospital in India - Roy, Nirmalya; Majumder, Anirban; Sanyal, Debmalya; Roy Chaudhuri, Soumyabrata; Sarkar, Suman; Pathak, Ankan (Journal of the ASEAN Federation of Endocrine Societies, 2020)
Myxedema coma is associated with decreased mental status and hyponatremia among patients with diagnosed or undiagnosed hypothyroidism. The diagnosis is challenging in the absence of universally accepted diagnostic criteria, but should be considered as a differential even in cases with competing established diagnoses. All patients should receive intensive care level treatment. Even with optimal treatment, mortality is very high.